PEMBERDAYAAN KERAJINAN BAJRA SEBAGAI MEDIA PENGANTAR UPACARA KEAGAMAAN HINDU KHAS BANJAR BUDAGA-KLUNGKUNG - I Gst B. Ngr. P. Putra; Ida Ayu Dinda Priyanka Maharani; Dewi Soraya; Anak Agung Ketut Jayawarsa (LPPM Institut Desain dan Bisnis Bali, 2023)
The people of Budaga Village preserve their ancestral heritage by engaging in handicraft arts, especially those made from brass metal. The types of handicraft products produced are generally related to Balinese Hindu ceremonial and ritual facilities such as the Dewata Nawa Sanga, Shiva Krana, sangku, anteg-anteg, gongseng and tray (bokor) weapons. However, the superior and typical craft product of Budaga Village is the bajra or bell craft. The bajra craft business that is carried out by the majority of the people of Budaga Village is still classified as a Micro, Small and Medium Scale Business, a home industry. Along the way, businesses with a small scope, such as the bajra craft business in Budaga Village, often experience business ups and downs. The main problem faced is increasingly tight product competition. The emergence of competitors for bajra producers from other areas, including outside Bali, is something that should be paid attention to. The second problem faced is limited capacity in recording financial transactions. Bajra entrepreneurs in Budaga Village often experience difficulties in determining cash inflows and outflows appropriately. The process of recording transactions is still done manually. The solutions offered for this problem are 1) Training in Recording Financial Transactions and Providing a Digitalized Financial Recording System; 2) Providing a Website as a Form of Marketing Strategy and Online Marketing Strategy Training.